Fabrication and study the effect of the laser on the properties of the compound Tl2-xHgxBa2-ySryCa2Cu3O10+Î´ superconductor - A. Kareem Dahash Ali; Nihad Ali Shafeek (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2018)
This study included the fabrication of    compound (Tl2-xHgxBa2-ySryCa2Cu3O10+Î´) in a manner solid state and under hydrostatic pressure ( 8 ton/cm2) and temperature annealing(850Â°C), and determine the effect of the laser on the structural and electrical properties elements in the compound, and various concentrations of x where (x= 0.1,0.2,0.3 ). Observed by testing the XRD The best ratio of compensation for x is 0.2 as the value of a = b = 5.3899 (A Â°), c = 36.21 (A Â°) show that the installation of four-wheel-based type and that the best temperature shift is TC= 142 K  .When you shine a CO2 laser on the models in order to recognize the effect of the laser on these models showed the study of X-ray diffraction of these samples when preparing models with different concentrations of the values â€‹â€‹of x, the best ratio of compensation is 0.2 which showed an increase in the values â€‹â€‹of the dimensions of the unit cell a=b = 5.3929 (A Â°), c = 36.238 (AÂ°). And the best transition temperature after shedding laser is TC=144 K.